Magnetic resonance imaging of ankle ligaments: A pictorial essay - Sawant, Yogini Nilkantha; Sanghvi, Darshana (Indian Journal of Radiology and Imaging, 2018)
Ankle trauma is commonly encountered and is most often a sprain injury affecting the ligaments. Accurate diagnosis and appropriate treatment rest on knowledge of complex ligamentous anatomy of ankle and the entire spectrum of pathologies. Magnetic resonance imaging (MRI) is the imaging modality of choice for diagnosing ligament pathologies because of its multiplanar capability and high soft tissue contrast. With MRI, it is possible to triage and attribute the cause of post traumatic ankle pain to bone, ligament, or tendon pathologies, which otherwise overlap clinically. In this pictorial essay, emphasis is given to the intricate and unique anatomy and orientation of ankle ligaments. Pathologies of ankle ligaments have been elaborated.
Keywords: Ankle ligaments; magnetic resonance imaging; sprain; tear